Protection schemes and settings of DC distribution systems. Issue 26 (26th February 2021) - Ke, Jia; Cong, Chen; Qijuan, Zhao; Tao, Feng; Tianshu, Bi; Haijun, Liu
Abstract : Flexible DC distribution system has become the research and development trend of the future distribution network with its unique advantages such as high efficiency and flexibility. However, the DC fault identification and protection is challenging due to the fact that the short‐circuit current provided by converters is limited and last for a very short period, how to identify and isolate faults reliably using limited fault transient information becomes a serious problem faced by system protection. Based on the analysis of the fault characteristics of three typical faults in the DC distribution system, the setting principle and the calculation methods are proposed, and the reasonable range of protection setting boundaries is derived. According to the requirements of protections, the parameters of the actual DC distribution system are used for setting calculations, and a complete set of DC line protection schemes is designed in this study. Finally, the performance of the proposed protection scheme is verified in PSCAD/EMTDC simulation platform, the built simulation model has been successfully applied to the analysis and calculation in the commissioning of the DC distribution system.